2009
DOI: 10.5751/es-02919-140218
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Provisioning Services of Wetlands: Contrasting a Rural Wetland in Lesotho with a Peri-Urban Wetland in South Africa

Abstract: Given that few studies have valued the provisioning services of temperate southern African wetlands, research on this topic was undertaken in a remote rural wetland, Letseng-la-Letsie, in Lesotho and a peri-urban wetland in Mfuleni, Cape Town. The objectives were to quantify incomes from wetland resources, assess the relative dependency of communities on wetland provisioning services, and estimate the total provisioning value of the wetlands. Data were collected from informal interviews and structured househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 19 publications
(21 reference statements)
4
18
0
Order By: Relevance
“…Wetland use activities provide a significant supplement to other sources of earnings, and often generate the only regular cash income for households. These results are consistent with other studies (Lannas and Turpie 2009;Rebelo et al 2010), but are considerably higher than that of some other African studies. For the Ga-Mampa wetland in South Africa 16% of the total value of the wetland was generated as cash income (Adekola et al 2012); 17% in the Barotse wetland, Zambia, 13% in the Chobe-Caprivi wetlands, and 15% in Malawi's Lower Shire wetlands (Turpie et al 1999).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Wetland use activities provide a significant supplement to other sources of earnings, and often generate the only regular cash income for households. These results are consistent with other studies (Lannas and Turpie 2009;Rebelo et al 2010), but are considerably higher than that of some other African studies. For the Ga-Mampa wetland in South Africa 16% of the total value of the wetland was generated as cash income (Adekola et al 2012); 17% in the Barotse wetland, Zambia, 13% in the Chobe-Caprivi wetlands, and 15% in Malawi's Lower Shire wetlands (Turpie et al 1999).…”
Section: Discussionsupporting
confidence: 82%
“…Monetary values per unit area ($/ha/year) and per household ($/hh) in our study are generally higher than those reported in these studies (Table 2), which is likely due to the extent of the Niger Delta wetlands, and the level of dependence of the local community upon them compared to the other smaller wetlands. For instance only 13% of households use the Mfuleni wetlands and 65% in Letseng-la-Letsie (Lannas and Turpie 2009) compared with 100% of households in our study. Furthermore, the Niger Delta has one of the highest population densities in the world for an area of comparable size (Ericson et al 2006;Balouga 2009) However, the total value of $12,500/ha/year from our study is consistent with global estimates for different types of wetlands (tidal marsh, mangroves, swamps and floodplains) which ranges from $13,786 -$193,843/ha/year (Costanza et al 2014).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We identified rooftop gardens during our survey. Based on the survey data we extrapolated total gross value of rooftop provisioning services for all holdings in the study area following equation 1 from Lannas and Turpie (2009)…”
Section: Valuation Mechanismmentioning
confidence: 99%
“…A substantial body of evidence demonstrates that wetlands can deliver a great variety of benefits to human society (Ghermandi et al 2010). These benefits include, but are not limited to, managing flood risk (Mitsch and Day, 2006), decreasing peak air temperatures (Sun et al, 2012), improving water quality (Shutes, 2001;Dhote and Dixit 2009), protecting coastal communities from storms (Gedan et al 2011), supporting food production (Lannas and Turpie, 2009;Verhoeven and Setter, 2009), providing vital cultural resources (McGregor et al 2010) and offering locations for a variety of education and recreation opportunities (Cachelin et al 2009;Finlayson et al 2013).…”
Section: Introductionmentioning
confidence: 99%